Effective Communication for Doctor-Patient Narrative Inquiry on TBC - Musli Ariani; Arief Rijadi; Agung Tjahjo Nugroho; Bonanza Vidya Rashmi Nugroho (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2023)
The community service aims at training the internship medical doctor on effective communication for doctor-patient narrative inquiry on TBC. This workshop was held due to need for the achievement on TBC contact investigation. Four-step training was conducted including exposure to effective communication and narrative inquiry, focus group discussion on problems and alternative solutions, peer doctor-patient communication practice, and reflection. The results of the current community service reveal that the achievement on TBC investigation rises due to the internship medical doctors willingness to do the follow through of the program. They have initially followed the standard norms of doctor-patient communication, and even improve their method of communication by utilizing their knowledge and understanding of the conversational maxims and use it in the narrative inquiry on TBC.